Da'i Kekinian: Mewujudkan Penyiaran Islam Komprehensif Berdasarkan Etika Komunikasi Al-Qur'ani - Muhamad Rif’at Syadli; Hilman Mauludin (Peneliti.net, 2022)
This study looks at the morals of correspondence in the viewpoint of the Qur'an and executes the virtues in it in the extent of da'wah for Islamic telecom, particularly in acknowledging current da'i who can teach completely while still in light of the morals of Qur'anic correspondence. This examination strategy is enlightening subjective, with a hermeneutic way to deal with comprehend sections containing the term correspondence, and dissect them with an Islamic da'wah way to deal with consider the peculiarity of the execution of da'wah in the cutting edge time. The outcomes show that the standards and morals of correspondence in the Qur'an are extremely suitable to be utilized as morals and techniques for teaching in the worldwide time, with the unique improvement of society, globalization of data and an elevated degree of savvy. , integrative and useful